Economic Evaluation on the Application of Collaborative Forest Management (CFM) - Waridin Waridin; Rizky Karunia Dhea Safira; Indah Susilowati; Kesi Wijajanti; Evi Yulia Purwanti (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
This study aims to analyze the collaborative forest management as well as the economic benefits obtained by forest village communities through intercropping of maize plants and cattle productive business. 80 respondents were selected through non probability sampling techniques with saturated sample methods. The research data was collected by conducting observations, in-depth interviews and distributing questionnaires to respondents and key informants. The data obtained were analyzed using descriptive analysis with quantitative methods consisting of income analysis, R/C ratio, co-management analysis and stakeholder analysis and productive business of cattle. The results show that the economic benefit of maize cropping obtained by Sumberejo village and Padaan Village has given them profit with an R/C ratio of 1.4 and 1.7. For cattle productive business, Sumberejo Village has gotten a profit with the R/C ratio over the total cost of 1.07 and Padaan Village has an R/C ratio of 1.00 (Break Even Point). Through the Mann Whitney statistical test there are differences in income between the sharing forest village (Sumberejo Village) and the non-sharing forest village (Padaan Village). Cattle productive businesses are found to have no difference in income values. Collaborative based forest management at the research location through the concept of co management analysis showed good results with a total score of 3.5 (close to 4). A co management approach is needed for better future forest management.